Management of ovarian ectopic pregnancy: a case report - Dhungana, Rakshya; Dangal, Binod; Neupane, Ayush (Journal of General Practice and Emergency Medicine of Nepal, 2023)
An ectopic pregnancy occurs when a developing blastocyst implants at places other than the uterine cavity. An incidence of ovarian implantation is 1 in 7000 to 40000 live birth and 0.5 to 3 % of all ectopic pregnancies.If ruptured, it is a life-threatening condition. We report a case of 30-year-oldmultiparous (G3P2L2) female who presented to us with chronic lower abdominal pain and irregular per-vaginal bleeding. She was diagnosed with differential ruptured ovarian pregnancy and a corpus luteal cyst on her left side and underwent laparotomy. During laparotomy, the diagnosis was confirmed to be left ruptured ovarian pregnancy which was later confirmed by the histopathological report. She underwent left-sided oophorectomy with preservation of the fallopian tube as it was normal.